2009
DOI: 10.1111/j.1745-4549.2008.00252.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensory and Physicochemical Quality of Pounded Yam: Varietal and Storage Effects

Abstract: Tubers from nine yam cultivars (Dioscorea rotundata, Dioscorea alata) collected in two different growing areas of Bénin were stored for up to 5 months. Pounded yam was prepared from tuber samples each month and evaluated for their sensory and physicochemical attributes in order to assess the effect of tuber storage on suitability for processing into the product. Irrespective of the initial tuber dry matter content, the dry matter content of pounded yam remained almost constant with a mean value of 23% (wet bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 14 publications
5
30
1
Order By: Relevance
“…Sensorial analysis confirmed that pounded yam prepared with Florido had very weak elasticity and smoothness in contrast to pounded yam prepared from other cultivars and particularly from Laboco (Akissoe et al, 2008). However, the instrumental measurements performed in this study failed to provide clear a Mean values (10 4 Pa) adjusted for 5 mm thickness and 5 mm width.…”
Section: Pounding Behaviourcontrasting
confidence: 60%
See 4 more Smart Citations
“…Sensorial analysis confirmed that pounded yam prepared with Florido had very weak elasticity and smoothness in contrast to pounded yam prepared from other cultivars and particularly from Laboco (Akissoe et al, 2008). However, the instrumental measurements performed in this study failed to provide clear a Mean values (10 4 Pa) adjusted for 5 mm thickness and 5 mm width.…”
Section: Pounding Behaviourcontrasting
confidence: 60%
“…Observations by processors have shown that preferred varieties have the ability to form mealy, elastic and smooth dough, while other varieties have a granular, non-homogeneous dough texture (Hounhouigan et al, 2003). Sensorial analyses confirmed that the ease of moulding and the springiness of the mass were the main positive attributes of pounded yam, whereas lumpiness (lack of smoothness) was the main reason for aversion (Akissoe, Mestres, Hounhouigan, & Nago, 2008;Nindjin et al, 2006). Recently, it was reported that the elasticity of pounded yam was linked to the dry matter content of the yam tuber (Akissoe et al, 2008).…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations